THE IMPACT OF USING INTERACTIVE MULTIMEDIA IN TEACHING BASIC BADMINTON TECHNIQUES TO IMPROVE COGNITIVE LEARNING OUTCOMES AND SELF-REGULATED LEARNING OF PHYSICAL EDUCATION STUDENTS - Ariani, Luh Putu Tuti; Marti, Ni Wayan (STKIP Citra Bakti, 2024)
The learning process demands high-quality human resources that evolve with the times. Technological development is essential for the learning process in the form of media. Interactive multimedia is a tool equipped with controls that can be operated by users as desired. This Interactive Media can facilitate learning, making it a stimulus to improve learning outcomes and self-regulated learning. The purpose of this study is to determine the effect of using interactive multimedia in teaching basic badminton techniques to improve cognitive learning outcomes and self-regulated learning among Physical Education students at FOK Undiksha. This research uses an experimental design with The Posttest-Only Control Group Design. The sample was selected using simple random sampling through a lottery method. The instruments for measuring learning outcomes involved a test of basic badminton skills and a questionnaire for assessing self-regulated learning. Data analysis for hypothesis testing required precondition tests, namely normality and homogeneity/F-tests. After conducting these precondition tests, hypothesis testing was carried out using a difference test. The results showed that the use of interactive media had a high impact on cognitive learning outcomes and self-regulated learning in basic badminton techniques. In conclusion, there is a significant difference in the learning outcomes of basic badminton techniques and self-regulated learning between Physical Education students at FOK Undiksha who were taught using interactive multimedia and those who were taught using conventional methods.